Epidemiological evaluation of measles cases seen in 2019-2023: an example from Türkiye - Tekdemir, Leyla; Özsaydı, Semiha Zeynep; Borlu, Arda (The Journal of Infection in Developing Countries, 2025)
Introduction: Measles is highly contagious and transmitted via droplets, leading to complications such as encephalitis, pneumonia, diarrhea, and death. Although global vaccination efforts have reduced cases, gaps in vaccination coverage and vaccine hesitancy continue to cause outbreaks. This study aims to evaluate measles cases reported in Kayseri, Türkiye, from 2019 to 2023. Methodology: The study analysed measles cases reported to the Kayseri Provincial Health Directorate’s İZCİ system from 1 January 2019 to 31 December 2023. Demographic characteristics, vaccination status, symptoms, complications, and case classifications were recorded. Annual incidence rates were calculated using data from the Turkish Statistical Institute. Results: A total of 137 measles cases were reported, of which 126 were included in the analysis. Among confirmed cases, 48.2% were children aged 0–4 years. The most common symptoms were rash (89.7%) and fever (81.0%). Among confirmed cases, 17.9% developed complications, including pneumonia (12.5%) and diarrhea (1.8%). The incidence of measles peaked in 2019 and 2023. Conclusions: The resurgence of measles is driven by factors such as inadequate vaccination coverage, with 35.7% of the population remaining unvaccinated. Strengthening immunization programs and primary healthcare services is essential for the elimination of measles.